2020
DOI: 10.4049/jimmunol.2000048
|View full text |Cite
|
Sign up to set email alerts
|

TRIM21 Is Targeted for Chaperone-Mediated Autophagy during Salmonella Typhimurium Infection

Abstract: Salmonella enterica serovar Typhimurium (S. Typhimurium) is a Gram-negative bacterium that induces cell death of macrophages as a key virulence strategy. We have previously demonstrated that the induction of macrophage death is dependent on the host's type I IFN (IFN-I) response. IFN-I signaling has been shown to induce tripartite motif (TRIM) 21, an E3 ubiquitin ligase with critical functions in autoimmune disease and antiviral immunity. However, the importance and regulation of TRIM21 during bacterial infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…TRIM21 was originally identified as an autoantigen in autoimmune diseases, including rheumatoid arthritis, Systemic lupus erythematosus, and Sjogren’s syndrome ( Schulte-Pelkum et al, 2009 ). TRIM21 acts as an important factor involved in the innate immune responses against microbial infection, including bacterial, viral, and parasite ( Hos et al, 2020 ; Mu et al, 2020 ; Xie et al, 2020 ), however, little about TRIM21 is known for parasites infection. In this study, we reported that T. gondii RH and CEP infection upregulated the expression of TRIM21, thus restricted parasite replication through NF-κB activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRIM21 was originally identified as an autoantigen in autoimmune diseases, including rheumatoid arthritis, Systemic lupus erythematosus, and Sjogren’s syndrome ( Schulte-Pelkum et al, 2009 ). TRIM21 acts as an important factor involved in the innate immune responses against microbial infection, including bacterial, viral, and parasite ( Hos et al, 2020 ; Mu et al, 2020 ; Xie et al, 2020 ), however, little about TRIM21 is known for parasites infection. In this study, we reported that T. gondii RH and CEP infection upregulated the expression of TRIM21, thus restricted parasite replication through NF-κB activation.…”
Section: Discussionmentioning
confidence: 99%
“…TRIM 21, also known as Ro52/SS-A, is involved in innate and acquired immunity against viruses and bacteria via the ubiquitination of interferon regulatory factors IRF3, IRF5, IRF7, and IRF8, but little is known about its role in parasitic infection ( Lazzari et al, 2014 ; Liu et al, 2018 ). Following Salmonella typhimurium infection, TRIM21 is also essential to promote cell death through conferring p62 ubiquitination and proteasomal degradation ( Pan et al, 2016 ; Hos et al, 2020 ). Furthermore, it has been reported that TRIM21 mediates NF-κB activation to aggravate the inflammatory response in psoriasis ( Yang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…One study found that TRIM11 promotes tumorigenesis and is regulated by Nrf2-one of the mechanisms is reducing oxidative stress during oncogenic growth [113]. The involvement of TRIM21 in the p62-Keap1-Nrf2 axis has been reported before [114][115][116]. Recently, TRIM21knockout mice were identified to be resistant to DENinduced hepatocarcinogenesis because the genetic ablation of TRIM21 protected cancer cells from oxidative hepatic damage [117].…”
Section: Cancer Type Low Expression Level High Expression Levelmentioning
confidence: 99%
“…For instance, ARIH1, LRSAM1, RNF213, and LUBAC are known to colocalize with damaged SCVs and promote cytosolic S. Typhimurium Ub coat formation. There is also a group of E3 ligases like RNF166 (Heath et al, 2016), MARCH8 (Jin et al, 2017), TRIM21 (Hos et al, 2020), TRIM22 (Lou et al, 2018), and TRIM16 (Chauhan et al, 2016) that do not recognize the pathogen itself but recognize other aspects of infection like exposed glycans (Chauhan et al, 2016).…”
Section: Mechanism Of Ubiquitin-mediated Xenophagymentioning
confidence: 99%